Uncovering a causal connection between the Lachnoclostridium genus in fecal microbiota and non-alcoholic fatty liver disease: a two-sample Mendelian randomization analysis - Dai, Wanhui; Cai, Dandong; Zhou, Shuai; Li, Ang; Xie, Jinsong; Zhang, Jie (Frontiers in Microbiology, 2023)
Background Previous observational studies have indicated that an imbalance in gut microbiota may contribute to non-alcoholic fatty liver disease (NAFLD). However, given the inevitable bias and unmeasured confounders in observational studies, the causal relationship between gut microbiota and NAFLD cannot be deduced. Therefore, we employed a two-sample Mendelian randomization (TSMR) study to assess the causality between gut microbiota and NAFLD. Methods The gut microbiota-related genome-wide association study (GWAS) data of 18,340 individuals were collected from the International MiBioGen consortium. The GWAS summary data for NAFLD from the Anstee cohort (1,483 cases and 17,781 controls) and the FinnGen consortium (894 cases and 217,898 controls) were utilized in the discovery and verification phases, respectively. The inverse variance weighted (IVW) method was used as the principal method in our Mendelian randomization (MR) study, with sensitivity analyses using the MR-Egger, weighted median, simple mode, and weighted mode methods. The MR-Egger intercept test, Cochran’s Q test, and leave-one-out analysis were conducted to identify heterogeneity and pleiotropy. Moreover, a fixed-effect meta-analysis was conducted to verify the robustness of the results. Results The gene prediction results showed that at the genus level, four gut microbiota were causally associated with NAFLD in the GWAS conducted by Anstee et al. The relative abundance of Intestinimonas (OR: 0.694, 95%CI: 0.533–0.903, p = 0.006, IVW), Lachnoclostridium (OR: 0.420, 95%CI: 0.245–0.719, p = 0.002, IVW), and Senegalimassilia (OR: 0.596, 95%CI: 0.363–0.978, p = 0.041, IVW) was negatively associated with NAFLD. The relative abundance of Ruminococcus1 (OR: 1.852, 95%CI: 1.179–2.908, p = 0.007, IVW) was positively correlated with NAFLD. Among them, the Lachnoclostridium genus was validated in FinnGen GWAS (OR: 0.53, 95%CI: 0.304–0.928, p = 0.026, IVW). The Lachnoclostridium genus was also significantly associated with NAFLD risk in the meta-analyses (OR: 0.470, 95%CI: 0.319–0.692, p = 0.0001, IVW). No heterogeneity or pleiotropy was observed. Conclusion This study provided new evidence of the relationship between the Lachnoclostridium genus and NAFLD, suggesting that augmentation of the relative abundance of the Lachnoclostridium genus through the oral administration of probiotics or fecal microbiota transplantation could be an effective way to reduce the risk of NAFLD.